2017
DOI: 10.1177/2042098617736191
|View full text |Cite
|
Sign up to set email alerts
|

Incident adverse drug reactions in geriatric inpatients: a multicentred observational study

Abstract: This feasibility study established the rates of incident ADRs across the six study sites. The ADR predictive power of ADRROP and GerontoNet ADR risk scales were limited in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 16 publications
0
24
0
1
Order By: Relevance
“…Prior to finalizing the trial protocol we conducted a non-interventional feasibility study at the same sites that are participating in the trial [23]. The feasibility study highlighted several challenges that led us to modify our initial trial design and our approach to the assessment of ADRs in the current trial.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to finalizing the trial protocol we conducted a non-interventional feasibility study at the same sites that are participating in the trial [23]. The feasibility study highlighted several challenges that led us to modify our initial trial design and our approach to the assessment of ADRs in the current trial.…”
Section: Discussionmentioning
confidence: 99%
“…This is in the range of previous studies describing the incidence of ADRs in geriatric patients admitted to hospital. 5861 As reported by others, 6265 electrolyte disorders and exsiccosis induced by diuretics, and falls associated with fall-risk-increasing drugs were the most common ADRs. A thorough medication review should result in a marked reduction of objectively measured and subjectively reported ADRs, as we prove in our intervention group.…”
Section: Discussionmentioning
confidence: 69%
“…To limit potential bias from selective ADR reporting and to ensure ADRs were not missed, a “trigger list” comprising the 12 most common drug‐related adverse events (AEs) was used . This list was derived from previous studies within our research group and aims to standardize the identification and classification of ADRs .…”
Section: Methodsmentioning
confidence: 99%